2021
DOI: 10.1038/s41598-021-00703-x
|View full text |Cite
|
Sign up to set email alerts
|

Human iPS cell derived RPE strips for secure delivery of graft cells at a target place with minimal surgical invasion

Abstract: Several clinical studies have been conducted into the practicality and safety of regenerative therapy using hESC/iPSC-retinal pigment epithelium (RPE) as a treatment for the diseases including age-related macular degeneration. These studies used either suspensions of RPE cells or an RPE cell sheet. The cells can be injected using a minimally invasive procedure but the delivery of an intended number of cells at an exact target location is difficult; cell sheets take a longer time to prepare, and the surgical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Quantitative knowledge is particularly helpful when designing scaffolds that actively utilise cellular detachment to engineer microtissues in three dimensions. For example, collective cellular detachment can be, if controlled, employed to create microtissues in unique 3D morphologies, such as strings [69] and bridges between piers [70]. Our modelling framework is in principle applicable to simulate cellular detachment from a scaffold in confined 3D environments, e.g., tubular structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative knowledge is particularly helpful when designing scaffolds that actively utilise cellular detachment to engineer microtissues in three dimensions. For example, collective cellular detachment can be, if controlled, employed to create microtissues in unique 3D morphologies, such as strings [69] and bridges between piers [70]. Our modelling framework is in principle applicable to simulate cellular detachment from a scaffold in confined 3D environments, e.g., tubular structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative knowledge is particularly helpful when designing scaffolds that actively utilise cellular detachment to engineer microtissues in three dimensions. For example, collective microtissue detachment can be, if controlled, employed to create microtissues in unique 3D morphologies, such as strings [58] and bridges between piers [59]. The mechanical understanding shown in this study would give deep insights into various aspects of scaffold design in tissue engineering, including scaffold geometry, surface treatments and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…RPE plays critical roles in vision by performing vital functions such as: (1) transporting nutrients, ions, and water to the PRs; (2) supplementing 11-cis-retinal in the visual cycle by isomerization of all-trans-retinal; (3) protecting against photooxidation and light absorption; (4) removing shed PR outer segment membranes with phagocytosis; and (5) secreting essential extracellular molecules (eg, laminin, collagen, and HA) to maintain retinal integrity, functionality, and PR viability. 106,107 Several studies used hESC/iPSC-derived RPE sheets (or "patches") for retinal degenerative therapy in animal models [108][109][110][111] and clinical trials [112][113][114][115] (reviews 116,117 ). These studies reported maintenance or improvement of visual function and delated RD.…”
Section: Transplant Cograft Of Rpe and Ro Sheetmentioning
confidence: 99%
“…Direct iPSC delivery through transplantation or injection has become the most studied approach in regenerative medicine [ 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. However, iPSC translational efforts have been dampened by concerns regarding the teratogenic potential of undifferentiated cells, as well as the lack of timely stimuli to carefully guide the in situ differentiation of these cells [ 108 ].…”
Section: Ipsc Generation and Cardiac Differentiationmentioning
confidence: 99%